RETHINKING HAMZAH FANSURI'S ISLAMIC COSMOLOGY - Fuad Mahbub Siraj (ILMU USHULUDDIN, 2021)
This study aims to explain further the cosmological argument of Hamzah Fansuri. This research is library research using a historical approach to obtain data and conduct content analysis. According to Hamzah Fansuri, every single thing in this world that either can or cannot be seen can be pictured as a circle or curvature, the two corners of which can meet each other. Half of the curvature is “the down way curvature” (tanazzul) that is the way of the creation of the universe and its content; the manifestation process from the Oneness or the Higher Existence (Who cannot be known physically) to become many existence or the reality that can be seen physically. The other curvature is “the up-way curvature” (taraqqī), which is a way of creation from physical to metaphysical existence. The entire levels or structure of being are summarized in the person and the human being’s existence as a perfect creature of physical and spiritual quality. Therefore, the universe can only be returned to the One through humans. The concept of cosmology in the Fansuri’s thought is to show the unity and interrelationship of all existence that leads to divine oneness.